Tính A= (-2)^0 + (-2)^1+ (-2)^2+ .............+(-2)^2004
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\left(-3\right)^0+\left(-3\right)^1+\left(-3\right)^2+.....+\left(-3\right)^{2004}\)
\(-3A=\left(-3\right)^1+\left(-3\right)^2+...+\left(-3\right)^{2005}\)
\(-3A-A=\left(-3^{2005}-\left(-3^0\right)\right)\)
\(A=\frac{\left(-3^{2005}-\left(-3^0\right)\right)}{-4}\)
Vì \(\left(x-2\right)^4\ge0;\left(2y-1\right)^{2004}\ge0\forall x;y\)
\(\Rightarrow\left(x-2\right)^4+\left(2y-1\right)^{2004}\ge0\forall x;y\)
Mà đề lại cho \(\left(x-2\right)^4+\left(2y-1\right)^{2004}\le0\Rightarrow\left(x-2\right)^4=0;\left(2y-1\right)^{2004}=0\)
\(\Rightarrow x=2;y=\frac{1}{2}\) Thay vào đa thức \(21x^{2y}+4xy^2\) ta được :
\(21.2^{2.\frac{1}{2}}+4.2.\left(\frac{1}{2}\right)^2=21.2+8.\frac{1}{4}=42+2=44\)
Đặt A=0-1+2-3+4-5+6-7+...+2004-2005
=(-1)+(-1)+.....+(-1)
Số số hạng -1 là:
\(\frac{\left(2005-0\right)\div1+1}{2}=1003\left(số\right)\)
Do đó A=1003(-1)
=-1003
Ta có : A = (12 - 22) + (32 - 42) + .... + (20032 - 20042) + 20052
= (1 - 2)(1 + 2) + (3 - 4).(3 + 4) + .... + (2003 - 2004).(2003 + 2004) + 20052
= -1(1 + 2 + 3 + 4 + .... + 2003 + 2004) + 20052
= -1.2004.(2004 + 1) : 2 + 20052
= -1002.2005 + 2005.2005
= 2005.1003 = 2011015